2015
DOI: 10.1038/gim.2014.213
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-exome sequencing reveals diverse modes of inheritance in sporadic mild to moderate sensorineural hearing loss in a pediatric population

Abstract: Purpose: This study was designed to delineate genetic contributions, if any, to sporadic forms of mild to moderate sensorineural hearing loss (SNHL) not related to GJB2 mutations (DFNB1) in a pediatric population. Methods:We recruited 11 non-DFNB1 simplex cases of mild to moderate SNHL in children. We applied whole-exome sequencing to all 11 probands. We used a filtering strategy assuming that de novo variants of known autosomal dominant (AD) deafness genes, biallelic mutations in autosomal recessive (AR) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…Although for the majority of this group the de novo mutation represented a single dominant hit causative of the phenotype, in one case the de novo mutation was in fact the second hit in an autosomal recessive form of retinitis pigmentosa. Similarly, in a cohort suffering from mild-to-moderate sensorineural hearing loss, de novo mutations were identified in two out of eleven sporadic cases [149], also suggesting a role for de novo mutations in this heterogeneous disorder.…”
Section: De Novo Mutations In Human Diseasementioning
confidence: 99%
“…Although for the majority of this group the de novo mutation represented a single dominant hit causative of the phenotype, in one case the de novo mutation was in fact the second hit in an autosomal recessive form of retinitis pigmentosa. Similarly, in a cohort suffering from mild-to-moderate sensorineural hearing loss, de novo mutations were identified in two out of eleven sporadic cases [149], also suggesting a role for de novo mutations in this heterogeneous disorder.…”
Section: De Novo Mutations In Human Diseasementioning
confidence: 99%
“…Various techniques, such as whole exome sequencing and targeted exome sequencing (TES), have made it possible to screen candidate genes in an extremely high-throughput manner. 1 However, making a conclusive molecular diagnosis still requires time and rigorous effort in many cases, particularly in nonsyndromic cases with rare variants. Thus, we recently suggested the importance of phenotype-driven genetic testing focusing on candidate genes according to the clinical phenotypes of the affected subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Severe-to-profound congenital or prelingual hearing loss results in the delay of language and behavioural development at an early age5. Therefore, early diagnosis of hearing loss should be mandatory in screening procedures such as newborn hearing screening.…”
mentioning
confidence: 99%
“…Whole exome sequencing (WES) has also been successfully used for analysis of genetic factors for hearing loss514, Additionally, WES has facilitated the identification of novel genes associated with Mendelian disorders including hearing loss151617. Recent studies have identified several causative genes for NSHL, including GPSM2, DNMT1, ELMOD3, GRXCR2 , and ADCY1 , by WES1516181920.…”
mentioning
confidence: 99%